A tale of two mountains: mountains in biblical spirituality. (1st January 2008) - France, Richard
<x content-type="archive" xml:space="preserve">Abstract</x> The article celebrates the symbolic importance of mountains. It considers the place of mountains in biblical thinking, as a pointer to the power and reliability of the God who made them. It focuses especially on two mountains, Sinai and Zion, and the contrasting ideologies associated with them in the Old Testament. It then notes the distinctive ways in which the New Testament exploits this contrast to symbolise the nature of Christian salvation, and suggests how modern spirituality, especially in a rural context, might draw on this symbolism.